Cultural Value the Dexterity Art of Fight Sheep as a Tourist Attraction in Garut Regency - Rima Safitri Suryadi; Fanny Agustina Hidayat; Ramdani Setiyariski (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: Indonesia is enjoying a positive trend in the tourism sector, supported by its natural and cultural wealth, making cultural tourism a favorite. One of the prominent cultural pearls is Garut Regency, with its unique ram fighting art and a reflection of the deep cultural values of its people. This study aims to identify and analyze the cultural value of the ram fighting art as a tourist attraction in Garut Regency. Research methods: This study uses a qualitative approach with an ethnographic focus in Pamidangan Arlamba and Anugrah Lembah Gunung Guntur. Results and discussion: The results of the study show that ram fighting is a tradition rich in symbolism, triggers sporting behavior, and is based on spiritual beliefs, offering authentic and educational experiences that contribute to the local economy and preservation. Implication: The developments needed are narrative education, authentic interactions, packaging of culture-based Events, improving facilities, and story-based promotions. It is hoped that the results of this study can be a guide to developing ram fighting as a sustainable, deep cultural experience for Garut.